Second NASA/ESA Conference on Adaptive Hardware and Systems (AHS 2007) 2007
DOI: 10.1109/ahs.2007.96
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reconfigurable Analog Arrays: Off-The Shelf Adaptive Electronics for Space Applications

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…In the experiments conducted, the GA core found atleast one globally optimal solution for many different parameter settings as shown in bold in Table VI. The authors also observed that the GA core found atleast two different globally optimal solutions, (x 1 =C2, y 1 =4A) and (x 2 =DB,y 2 =4A), during the experimental run with RNG seed=(AAAA) 16 , population size=64, and crossover threshold=10. Figure 9.…”
Section: Modified 2d Shubert Functionmentioning
confidence: 87%
See 2 more Smart Citations
“…In the experiments conducted, the GA core found atleast one globally optimal solution for many different parameter settings as shown in bold in Table VI. The authors also observed that the GA core found atleast two different globally optimal solutions, (x 1 =C2, y 1 =4A) and (x 2 =DB,y 2 =4A), during the experimental run with RNG seed=(AAAA) 16 , population size=64, and crossover threshold=10. Figure 9.…”
Section: Modified 2d Shubert Functionmentioning
confidence: 87%
“…This can be very useful in space and military applications where human intervention needs to be minimized. In [16], Zebulum et al proposed a Self-Reconfigurable Analog Array (SRAA) architecture that used multiple building blocks to build different analog circuits including Pulse Width Modulator, Power Switch Control, Shaft Encoder, and Instrumentation Amplifier. They identified a list of analog building blocks such as Op-Amps, Low offset Op-Amps, High Voltage Op-Amp, Current Source, Comparator, and High-speed Comparator and implemented them in as a Reconfigurable Analog Array ASIC.…”
Section: Self Reconfigurable Analog Electronicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, it is possible to distinguish between analog EHW systems, mixed analogdigital EHW systems, and digital EHW systems. Analog EHW systems are based on either Field Programmable Transistor Arrays (FPTA) or Field Programmable Analog Arrays (FPAA) [Terry et al 2006;Zebulum et al 2007]. Mixed analog-digital EHW systems, instead, rely on custom devices (e.g., the Evolvable Motherboard described by Layzell [1998]) and can be used to develop circuits composed of both digital and analog parts.…”
Section: Evolvable Hardware: Taxonomymentioning
confidence: 99%